PENGARUH SEDUHAN BUNGA TELANG (CLITORIA TERNATEA) TERHADAP LDL (LOW DENSITY LIPOPROTEIN) WANITA MENOPAUSE DI WILAYAH BONTANG - Wiwik Susianti; Nilam Noorma; Indah Nur Imamah (Bajang Institute, 2024)
Introduction: Menopausal women experience a decrease in the hormone estrogen which plays an important role in controlling cholesterol levels and functions as an antioxidant. The role of estrogen as an antioxidant is to prevent the LDL oxidation process so that LDL's ability to penetrate plaque is reduced. High LDL levels require treatment, one of which is non-pharmacological treatment using infusion of telang flowers. There is a growing phenomenon regarding the benefits of butterfly pea flowers, especially in lipoprotein oxidation, which is very beneficial for consumption by menopausal women. This study aims to determine the effect of steeping telang flowers on LDL levels in menopausal women. Method: The research design was pre-experimental using a quantitative type of research, the population studied were all menopausal women who had LDL levels ˃ 100mg/dl and did not take cholesterol medication, the sample size in the study was 16 people (pre-post) using the Federer formula. The instrument used is an observation sheet with a paired sample T test. Results: analysis shows ρ value 0.026˂ 0.05, meaning Ho is rejected and Ha is accepted so that there is an influence of giving telang flower infusion on LDL levels in menopausal women in the Bontang area. Conclusion: There is a difference in the pre-test LDL results of drinking telang flower infusion and the post-test LDL results of drinking telang flower infusion in the Bontang Community Health Center area.